Research on the Impact of Actual Tax Bearing Rate on the Financial Performance of Enterprises - Dong, Yao; Liang, Chen; Wanyin, Zhong (Frontiers in Public Health, 2022)
This paper is based on financial data analysis of 241 listed pharmaceutical manufacturing enterprises in China, we study the different effects of different tax reduction policies on the financial performance of enterprises in the short term and long term. Through the verification of practical examples, it could be found that the implementation of a tax reduction policy can indeed play a positive role in the financial performance of enterprises, and the reduction of income tax significantly improves the short-term financial performance of enterprises. However, the tax reduction of turnover tax significantly enhances the long-term financial performance of enterprises, and the effect of tax reduction on the financial performance of state-owned enterprises is better than that of non-state-owned enterprises. Generally speaking, tax reduction policy has a better effect on the financial performance of non-state-owned enterprises and enterprises in central and western regions than state-owned enterprises and enterprises in eastern regions.